The wealth effect in the Eurozone - Rodil-Marzábal Óscar; Menezes-Ferreira-Junior Vicente (Panoeconomicus, 2016)
The recent global financial crisis represents a serious threat to the growth of economies. This crisis deeply affects the real economy through a phenomenon known as the wealth effect, which assumes that a fall in wealth leads to a reduction of private consumption. Thus, this paper analyzes the wealth effect on consumption using quarterly macro-data for 10 Eurozone countries in the period 2000-2010. The results suggest the existence of a positive and significant wealth effect on consumption with the predominance of a financial effect on housing, showing larger consumption sensitivity to changes in the value of financial assets.